2017
DOI: 10.1126/sciadv.1700241
|View full text |Cite
|
Sign up to set email alerts
|

Distinct properties of the triplet pair state from singlet fission

Abstract: The triplet pair from singlet fission is characterized by distinct spectroscopic signature and can be difficult to break apart.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
171
1
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 112 publications
(199 citation statements)
references
References 66 publications
18
171
1
5
Order By: Relevance
“…Global target analysis has been applied to model singlet fission dynamics of a number of chemical and material systems, including those that are disordered. 3 6 , 50 , 54 , 83 , 86 , 111 117 Unlike previous models of singlet fission dynamics in disordered systems which have exclusively accounted for sequential dynamics (and have thus ignored potential sample heterogeneity), 3 , 4 , 6 , 25 , 68 , 81 83 , 85 , 91 , 114 , 117 , 118 the six-component kinetic scheme presented here accounts for the parallel decay of two sets of sub-populations. Parallel decay pathways can especially be manifested in systems where multiple packing arrangements or conformations exist within the potential energy landscape 119 , 120 and additionally where the underlying sub-populations exhibit overlapping ground-to-excited-state absorption spectra (see e.g.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Global target analysis has been applied to model singlet fission dynamics of a number of chemical and material systems, including those that are disordered. 3 6 , 50 , 54 , 83 , 86 , 111 117 Unlike previous models of singlet fission dynamics in disordered systems which have exclusively accounted for sequential dynamics (and have thus ignored potential sample heterogeneity), 3 , 4 , 6 , 25 , 68 , 81 83 , 85 , 91 , 114 , 117 , 118 the six-component kinetic scheme presented here accounts for the parallel decay of two sets of sub-populations. Parallel decay pathways can especially be manifested in systems where multiple packing arrangements or conformations exist within the potential energy landscape 119 , 120 and additionally where the underlying sub-populations exhibit overlapping ground-to-excited-state absorption spectra (see e.g.…”
Section: Resultsmentioning
confidence: 99%
“…6b and c and 7 thus highlight the so-called “dual singlet-triplet optical character” of triplet pairs, originally reported in concentrated solutions of a tetracene derivative 88 and nanoparticle suspensions of pentacene derivatives, 5 that has also been observed in covalently-tethered tetracene and pentacene pairs. 3 , 6 , 81 A simple, coherent and unifying explanation of the origin of this dual singlet-triplet optical character, however, has yet to be provided.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They represent the fundamental smallest number of chromophores required for SF and varying the connectivity between the chromophores can lead to insightful structure-property relationships of the constrained excitons, from the generation, [19][20][21][22] separation, [23][24][25][26] and recombination [27][28][29][30] of triplet states, to the elucidation of the bound triplet pair state. [31][32][33][34] It has been established that molecular vibrations play a key role in mediating singlet ssion in both oligoacene molecular crystals (intermolecular singlet ssion, xSF) and in acene intramolecular singlet ssion (iSF) compounds. 17,[35][36][37][38] In crystals, it is now commonly accepted that both coherent and incoherent formation of triplet pairs is possible, even within the same system.…”
Section: Introductionmentioning
confidence: 99%
“…Contiguous dimers have shown that the singlet and triplet pair energy manifolds are mixed, with allowed TT-S n optical transitions. 32,62 Furthermore, radiationless decay of triplet pairs has been shown to slow down as chromophore proximity decreases. From this, we suggest that the triplet pair decays through coupling to singlet vibronic modes, permitting a rapid and spin-allowed route back to the ground state.…”
Section: Introductionmentioning
confidence: 99%